Diagnostic value of cytokine profiles in children with atopic bronchial asthma and concurrent vitamin D deficiency - Sultanova, Naila; Jafarova, Aytan; Karimova, Rana; Orujov, Mushfig; Gafarov , Ismail (Acta Biomedica Atenei Parmensis, 2025)
Atopic bronchial asthma in children is often associated with immune dysregulation and altered cytokine profiles. To assess the sensitivity and specificity of cytokines against the background of vitamin D deficiency in children with atopic bronchial asthma. A total of 85 children (59 boys, 26 girls) aged 4-17 years with atopic bronchial asthma were monitored at two medical centers in Baku. Inclusion criteria required a minimum disease duration of two years and a history of recurrent asthma attacks. Data were collected retrospectively from medical records. The control group consisted of 20 healthy children (12 boys, 8 girls). Sample sizes for both groups were calculated using the formula: n = (t² σ²) / δ² to ensure adequate statistical power. The general diagnostic values (GDV) were: IL-2 – 93.8 ± 3.0%, IL-13 – 90.6±3.6%, and IL-17 – 95.3±2.6%. The diagnostic accuracy of both positive and negative test results was evaluated, with positive results rated as ’excellent’ and negative results as ’good’ for these cytokines. A significant positive correlation was found between vitamin D deficiency and IL-2, while IL-13 and IL-17 showed negative correlations with vitamin D in the patient group. Levels of pro-inflammatory cytokines IL-13 and IL-17 were significantly higher in children with bronchial asthma compared to controls (p < 0.01). Specifically, mean serum IL-13 concentration was 13.8 ± 0.8 pg/ml in patients versus 5.3 ± 0.7 pg/ml in controls. While the correlations between vitamin D levels and cytokines (IL-2, IL-13, IL-17) were statistically significant, their moderate strength suggests the possible influence of additional contributing factors. Significant correlations between vitamin D status and cytokine levels highlight the potential of IL-2, IL-13, and IL-17 as biomarkers of disease severity and therapeutic targeting. These results suggest that routine assessment and correction of vitamin D deficiency should be considered an integral part of childhood asthma management.